Evaluación de los efectos biopsicosociales de covid 19 en escolares de la unidad educativa Alejandro R. Mera Tulcán - Anrango Benavides, Angela Estefanía (2025)
The objective of this research was to implement preventive strategies that contribute to reducing the biopsychosocial effects of COVID-19 in students of the Alejandro R. Mera Tulcán Educational Unit. For this, theoretical-level methods such as synthetic analytical, historical-logical, inductive-deductive and empirical methods were used, such as the observation through which the first contact with the study problem was had. The paradigm used was mixed quali-quantitative, supported by descriptive, bibliographic, and correlational research. The research instrument was the questionnaire, which was applied to the students of the institution, obtaining among the main results that 35% of them presented feelings of loneliness and anxiety about isolation in 29%, in addition to depression, stress among others; combined with the fact that 75% mentioned not having had their mental health followed up during homeschooling; Likewise, this new way of life has caused changes in eating habits, sleep disorders, as well as an increase in learning difficulties by 65%, which represents a high risk to the health of the infant, both physically and emotionally. That is why a series of strategies focused on reducing the biopsychosocial effects caused by COVID-19, providing parents with the necessary knowledge to be able to face this type of situation.